LINGUCULTUROLOGICAL PROPERTIES OF MEDICAL UNITS OF UZBEK LANGUAGE. - Gaybullaevna, Navruzova Muyassar (The journal of contemporary issues in business and government, 2021)
This article is devoted to the study of physician’s communication manner, medical deontology, doctor-patient relationship, the relationship of doctor with the relatives of patient, medical ethics, the role of psychotherapy in physician’s work, linguocultural aspect of medical language, the linguocultural speech result of euphemism.